If it's not what You are looking for type in the equation solver your own equation and let us solve it.
0=-6b-5b
We simplify the equation to the form, which is simple to understand
0=-6b-5b
We move all terms containing b to the left and all other terms to the right.
+6b+5b=-0
We simplify left and right side of the equation.
+11b=0
We divide both sides of the equation by 11 to get b.
b=0
| .6*k+5=7 | | 3x^2-14x-2=0 | | -3x+9=-6y | | -7x-9(-3)=63 | | x-9=-7+5 | | 4n-n=-12 | | x-9/3=5 | | x^4-5x^2-50=0 | | 3-5(2x-1)+1x=-10 | | 7(7y+2)-9=-2 | | -5y-9=-y+1 | | 6(c+4c)=4c-18 | | 6x+4(4x-15)=50 | | -2=w/5 | | 3k-9=7+2k-k | | -4x+4(2x+8)=-8+8(x+8) | | L+50=1.32 | | -8/9(9+y)=64 | | 5/3x+1/3x=8/3+8/3x | | -8(t-7)-7(2t+1)=-17 | | 7(x-4)=6(x+1)-3 | | 5(40-(40-x))+10(40-x)+25x=405 | | -59=-5(4a-4)+1 | | -x-(13+4x)=-3(5-9k)+2 | | -0.8(2x-6)=1.7(3-x) | | 3y+(-11y)= | | 12x^2-81x-3/7=0 | | x/3-9=11 | | 12x^2-81x-3/7 | | -15t-9+8t=4t-3 | | 4+-1x=-1x+4 | | 0.5x-0.1=0.4-0.6(9-2x) |